Perioptic cyst distal to optic nerve meningioma: MR demonstration. - Lindblom, B; Norman, D; Hoyt, W F (American Journal of Neuroradiology, 1992)
Dilation of the subarachnoid space between the distal edge of an optic nerve sheath meningioma and the eyeball has previously been observed during surgery and considered a rare finding. We observed such perioptic cysts in seven patients with optic nerve meningioma and describe the MR features of this finding.